Lemna Minor influence in the treatment of organic pollutionof the industrial effluents - Alvarado Perez, Karina Milagros (2020)
The purpose of the research was to determine the influence of industrial wastewater treatment using the Lemna Minor aquatic plant. Certain varieties of macrophyte plants can absorb or retain various contaminants. Thanks to this, it has been determined that the variety known as Lemna Minor presents this type of property. Three treatment trials were carried out varying the amounts of Lemna Minor (100, 200, and 300g). They are keeping constant the retention time of 10 days that were analyzed at 3, 6, and 10 days after the treatment and with a constant volume of the residual effluent. The results indicate that in terms of the parameters that determine organic contamination, BOD was reduced by (61 %); COD was reduced by (68 %) and the concentration of total suspended solids by (61 %).